PENGARUH PERTUMBUHAN EKONOMI, PENGANGGURAN DAN PENDIDIKAN TERHADAP KEMISKINAN DI KABUPATEN BANGLI - Ria Suadnyani, Ni Wayan; Darsana, Ida Bagus (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 7, No. 5, Mei 2018 (pp. 868-1111), 2018)
The phenomenon of poverty is one of the macroeconomic diseases faced by countries in the world including Indonesia. Poverty has become a complex and chronic problem both at the national and regional levels, so that mitigation requires an appropriate and sustainable strategy. This study aims to analyze the influence of economic growth, unemployment and education simultaneously and partially to poverty in Bangli regency. Data used in this research is secondary data. The analysis technique used in this research is multiple linear regression analysis, which is accompanied by classical assumption test. The test result with SPSS obtained the result that simultaneously variable of economic growth variable, unemployment and education simultaneously have a significant effect on unemployment in Bangli regency. Partially, the variable of economic growth and education have negative and significant effect to poverty in Bangli regency. While unemployment variable have positive and significant effect to poverty in Bangli regency.